The effect of disinfectants on the surface quality of irreversible hydrocolloid impression material and gypsum cast - Dulaimi, suha; Al-Wahab, zahraa (Iraqi National Journal of Nursing Specialties, 2012)
Objective: To evaluate the changes in the surface quality of irreversible hydrocolloid impression materialhydrogum following disinfection with 0.525% sodium hypochlorite, 0.2% Chlorehexidine Gluconate, and 4%Povidone Iodine.Methodology: Forty specimens of alginate impression materials hydrogum were fabricated according to theISO 1563 and were divided into four groups according to the method of solution dipping: group 1: Dip in0.525% sodium hypochlorite, group 2: Dip in 0.2% chlorhexidine gluconate, Group 3: Dip in 4% Povidone Iodine,Group 4: No treatment with any solution (control group). Then the specimens were poured in type II stone.Surface detail was determined using a stainless steel block in accordance with ISO 1563.Results: The results were subjected to Kruskal – Wallis non parametric test showed no statistical significantdifference in the effect of the disinfection solution on the surface detail quality (P – value 0.392, at p> 0.05).However, the surface quality of the specimens disinfected by sodium hypochlorite showed some degree oferosion or damage to the surface quality of the resultant cast, but the difference was not statisticallysignificant.Recommendations: make microbiological study to evaluate the effect of disinfectant solutions on differentmicroorganisms present in the oral cavity and evaluate the hardness of impression material following the useof disinfectant solutions.